Responses of carbon dynamics to grazing exclusion in natural alpine grassland ecosystems on the QingZang Plateau - Liu, Tianyuan; Sun, Jian; Chen, Youchao; Zhou, Tiancai; Shang, Hua; Wang, Yingxin; Wu, Junxi; Mi, Qi; Zhang, Jintao; He, Wen; Sun, Le (Frontiers in Plant Science, 2022)
In the context of “Carbon Emissions Peak” and “Carbon Neutrality”, grazing exclusion (GE) has been applied widely to rehabilitate degraded grasslands and increase carbon sequestration. However, on the QingZang Plateau (QZP), the impacts of GE on the carbon dynamics of alpine grasslands are poorly understood, particularly at a regional scale. To fill this knowledge gap, we evaluated the responses of carbon sequestration to GE in different alpine grasslands across QZP by using meta-analysis. The effects of GE on ecosystem carbon fractions were dependent on GE duration, grassland types and climate factors. Specifically, our results indicated that GE had more obviously positive effects on carbon stock across the alpine meadow than the alpine steppe. However, when considering different GE duration, the longer duration of GE was more effective for increasing ecosystem carbon sequestration (R2 = 0.52, P<0.0001) in the alpine steppe. Our results further demonstrated that annual mean precipitation (AMP) and temperature (AMT) began to dominate ecosystem carbon sequestration after three years of GE duration across the alpine meadow; and AMP was an important climate factor limiting ecosystem carbon sequestration (R2 = 0.34, P<0.01) in the alpine steppe. In terms of plant carbon fraction, GE generated continuous positive effect (P<0.05) on aboveground biomass with the increased GE duration in the alpine meadow, while this positive effect disappeared after the 8th year of GE duration. And no positive effects were found on belowground biomass in the 11th year in alpine steppe. For soil organic carbon (SOC), there existed periodic fluctuations (increased and then decreased) on SOC in response to GE. For microbial biomass carbon, there were no obvious trends in response to GE duration. In general, we highlighted that the responses of different carbon fractions (plant-soil-microbe) to GE were non-uniform at spatial and temporal scales, thereby we should adopt different carbon management practices for sustainable development of different grasslands.